Dealing with Difficult People Fast, effective strategies for handling problem people - Lilley, Roy (Creating success, 2002)
Learn how to navigate the bullies, manipulators and complainers who drive you mad. With example dialogue and techniques, it will help you navigate tricky situations and keep your cool. By understanding the motives and individual behaviours of difficult people, you can learn to manage aggression, reduce awkwardness and remain the better person. This 5th edition of the bestselling Dealing with Difficult People features practical exercises, useful templates and top tips you need to get the best out of the worst, including how to deal with difficult customers, dealing with difficult people in the digital sphere, advice on beating bullies at their own game and how to deal with a boss who drives you barmy.